(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Postmenopausal bleeding is a significant clinical condition requiring prompt evaluation to exclude endometrial malignancy. Endometrial cancer is among the most common gynecological cancers, and early detection is crucial for improving prognosis. Conventional assessment using endometrial thickness lacks specificity, prompting the need for more comprehensive approaches. The International Endometrial Tumor Analysis criteria provide a standardized, multiparametric ultrasound-based evaluation. Aim & Objective: This study aimed to compare the diagnostic efficacy of IETA criteria with endometrial thickness using histopathology as the gold standard. Material & Methods: A prospective observational study was conducted over 18 months at a tertiary care center, including 62 postmenopausal women presenting with bleeding per vaginum. All participants underwent detailed clinical assessment, transvaginal ultrasonography evaluating endometrial thickness and IETA parameters, followed by histopathological examination through biopsy or hysterectomy. IETA assessment included echogenicity, endo-myometrial junction, midline appearance, intracavitary fluid, and Doppler vascularity. Diagnostic performance was analyzed using sensitivity, specificity, predictive values, and accuracy. Results: Among 62 patients, 11 cases were confirmed as endometrial carcinoma. IETA demonstrated higher sensitivity (83.68%) and specificity (39.22%) compared to endometrial thickness (81.82% and 18%, respectively). The overall diagnostic accuracy was greater with IETA (47.6%) than with endometrial thickness (30%). IETA also showed a high negative predictive value (90.92%), indicating reliability in ruling out malignancy. Ultrasound features such as heterogeneous echotexture, irregular endo-myometrial junction, and increased vascularity showed a strong association with malignancy. Conclusion: IETA criteria outperform endometrial thickness alone in evaluating postmenopausal bleeding by providing improved sensitivity and diagnostic accuracy. However, both methods have limited specificity and should not be used independently. A combined approach incorporating IETA with histopathological correlation enhances diagnostic reliability and aids in appropriate clinical decision-making.